`A Cloud Turned Goose': Sanskrit in the vernacular millennium - Yigal Bronner and David Shulman (Indian Economic Social History Review 2006; 43; 1, 2006)
A vast corpus of Sanskrit poetry (k.vya) was produced over the last thousand years; most of these works reveal a vital and organic relation to the crystallising regional traditions of the subcontinent and to emerging vernacular literatures. Thus we have, for example, the Sanskrit literatures of Kerala, of Bengal-Orissa, of Andhra, and so on. These works, often addressed primarily to local audiences, have remained largely unknown and mostly undervalued, despite their intrinsic merits and enormous importance for the cultural history of India. We explore the particular forms of complex expressivity, including rich temporal and spatial modalities, apparent in such poems, focusing in particular on Vednta De_ika.s Ham. sasande_a, a fourteenth-century messenger-poem modelled after K.lid.sa.s Meghasande_a. We hypothesise a principle: as localisation increases, what is lost in geographical range is made up for by increasing depth. Sanskrit poetry thus comes to play a critical, highly original role in the elaboration of regional cultural identities and the articulation of innovative cultural thematics; a re-conceptualised ecology of Sanskrit genres, including entirely new forms keyed to local experience, eventually appears in each of the regions. In short, rumours of the death of Sanskrit after 1000 A.D. are greatly exaggerated.